Greenhouse gas emissions from a land use change activity during a haze episode in Southeast Asia - Mastura Mahmud (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2008)
Carbon dioxide is by far the dominant greenhouse gas released from biomass burning activities for agricultural purposes, which can lead to a global warming potential if emissions to the atmosphere were left uncontrolled. The emissions of greenhouse gases from Sumatera, Indonesia during a major haze episode that occurred in August 2005 were investigated. The highest rate of burning occurred mainly in the province of Riau during the first two weeks of August. Total greenhouse gases emitted were estimated from the active fire counts derived from the NOAA satellite. During the haze episode that hit the western coast of Peninsular Malaysia, much green house gases such as carbon dioxide, carbon monoxide, nitrous oxide and methane were emitted to the atmosphere. The dispersion patterns of one the greenhouse gases during the height of the haze episode showed the path of transportation of the gas and the locations affected within the vicinity of the sources. The emission and transportation of the greenhouse gases, mainly carbon monoxide, from the biomass burnt in Sumatera also increased the local concentration in Peninsular Malaysia